Fenomena Kuliner Jepang di Indonesia: Antara Tren, Budaya, dan Adaptasi - Fatimah, Rezki; Panjaitan, Lilis Lamsehat (Vocational College of Diponegoro University, 2025)
Japanese cuisine has emerged as one of the most rapidly growing food trends in Indonesia over the past decade. This article explores the phenomenon of Japanese cuisine in Indonesia, focusing on trends, cultural influences, and local adaptations. Through a comprehensive analysis of literature and previous research, this study identifies gaps in existing research and offers novel insights into how Japanese cuisine has been adapted to fit the local context. The methodology employed includes qualitative analysis of data gathered from various sources, including academic articles, related books and research reports. The results of this study indicate that Japanese cuisine is not only embraced but also uniquely adapted by Indonesian society. It reflects a complex interplay between global culinary trends and local cultural identities. Thus, it can be concluded that the acceptance and adaptation of Japanese cuisine by Indonesian society reflect a dynamic process of acculturation, in which global culinary elements are reinterpreted to align with local tastes and cultural values. This highlights that cuisine is not merely a means of consumption, but also a medium of cultural interaction that expresses the identity and creativity of local communities in responding to global influences.